The relevant market in international economic law : a comparative antitrust and GATT analysis - Melischek, Christian A. (Cambridge : Cambridge University Press, 2013)
'This book provides what international trade law has hitherto lacked: a coherent analysis of'product likeness' under Article III of the GATT. Christian A. Melischek develops an economic approach to the interpretation of'like' products on the basis of a comparative analysis with antitrust theories on market definition. Not only does he propose a specific substantive economic test to render the notion of product likeness operational, but he also examines the institutional and procedural frameworks for expert economic evidence necessary to implement an economic approach to the interpretation of product likeness. On a methodological level, the book adds a new interdisciplinary dimension to the legal debate by exploring the use of quantitative and econometric methods for the implementation of the proposed economic test.'--Publisher's website.
Comparison of antitrust and international trade law -- The role of market definition -- Analytical evolution from the traditional to the economic approach -- Conceptualizing an economic approach to market definition -- The implementation of an economic approach : quantitative methods.
'Revised and updated version of ... [author's] doctoral thesis ... accepted by the University of Hamburg, Faculty of Law, in 2011'--Page xiii.
Includes bibliographical references (pages 339-363) and index.
Keywords: International economic relations; Foreign trade regulation; Antitrust law